How elite coaches' experiential knowledge might enhance empirical research on sport performance - A Commentary - Wulf, G. (International Journal of Sports Science and Coaching, 2012)
In their article, Greenwood et al. present interview data to demonstrate coaches` insights into factors influencing athletes` performance, and they suggest that researchers utilize coaches` knowledge when planning and designing studies related to learning and performance in sports. As evidence for coaches` unique insight into factors relevant to athletic performance, Greenwood et al. cite coaches` observations related to the run-up (e.g., track and field, gymnastics), the interaction of various constraints during performance (e.g., weather, fatigue, arousal), and individual differences (e.g., physical, cognitive, emotional). There may indeed be many instances in which contributions to knowledge in general, and an athlete`s or team`s success specifically, would be enhanced by paying close attention to experienced and expert observers such as coaches or athletes. Thus, I agree that their observations may well provide ideas for research studies. I also see some potential limitations, however. My thoughts related to the arguments put forward by Greenwood et al. are related primarily to two issues: a) the fact that coaches` observations seem to be shared by others, and b) that potentially false assumptions should be considered when designing research studies based on practitioners` knowledge.